PERANCANGAN SMART DOOR LOCK BERBASIS RFID DAN KEYPAD - Fathiah, Fathiah; Maulana, Hafidz; Baihaqi, Baihaqi; Mursyidin, Mursyidin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Security and security are important issues in everyday life. Using simple authentication systems such as mechanical keys has proven vulnerable to breaches. RFID technology and keypads are considerable solutions to this problem. The research aims to design and implement a smart door locking system that combines RFID and keypad technology to enhance room security. System design is based on ease of use, reliability, and security. The system is designed with a higher level of security, i.e. by combining RFID, keypad, and PIR sensors so that to open the door it requires an RFID scan, inserting a pin on the keypad and moving hands or something else to detect movement by the PIR sensor. The evaluation of usability shows that the system is well accepted by users with an average of 4.2 on the 5th scale.